Uncertainty and unwillingness to receive a COVID-19 vaccine in adults residing in Puerto Rico: Assessment of perceptions, attitudes, and behaviors - Andrea López-Cepero; Stephanie Cameron; Lyz E. Negrón; Vivian Colón-López; Uriyoán Colón-Ramos; Josiemer Mattei; Emma Fernández-Repollet; Cynthia M. Pérez (Human Vaccines & Immunotherapeutics, 2021)
Background: Widespread vaccination against COVID-19 is essential to control the pandemic. Estimates of unwillingness and uncertainty toward COVID-19 vaccination and factors associated with it remain unclear among adults in Puerto Rico (PR). Objective: To examine factors associated with uncertainty and unwillingness of COVID-19 vaccination among adults in PR. Methods: The Health Belief Model was used to develop an online survey. Analyses included adjusted logistic regressions (aOR). A total of 1,911 adults completed the survey from December 2020 to February 2021. Results: Overall, 76.2% were females, 33.7% were aged 50 or older, and 82.7% reported an intent to get vaccinated. Individuals who did not perceive that their chances of getting COVID-19 were high (aOR = 2.94; 95%CI = 2.24–3.86), that getting COVID-19 was not a possibility for them (aOR = 2.86; 95%CI = 2.19–3.74), or unafraid of getting COVID-19 (aOR = 3.80; 95%CI = 2.76–5.23) had higher odds of uncertainty and unwillingness to get vaccinated against COVID-19. Participants who perceived that COVID-19 complications were not serious also had higher odds of uncertainty and unwillingness (aOR = 7.50; 95%CI = 3.94–14.3), whereas those who did not perceive that they would get very sick with COVID-19 had 89% increased odds. Those who agreed that they would only take the vaccine if many individuals took it had higher odds of uncertainty and unwillingness (aOR = 3.32; 95%CI = 2.49–4.43). The most reported reasons for uncertainty and unwillingness toward COVID-19 vaccination were vaccine safety (63.8%), efficacy (49.4%), and novelty (45.5%). Discussion: Although COVID-19 vaccination intent was high, the study highlights concern over vaccine safety and efficacy that should be addressed by public health campaigns and interventions to enhance vaccine uptake.